Evaluation of the effect of omega-3, zinc and vitamin C on peri-implant bone density using cone-beam computed tomography and digital intra oral radiography - Mahmoud Aly Gamal Eldin Abdelaal; Hassan Sadek; Mochira Salah Eldin; Mushira Dahaba (Cairo : Mahmoud Aly Gamal Eldin Abdelaal, 2011)
The exact mechanism of the dietary intake on bone metabolism needs further histopathological and bone morphmetric studies in animals. Further investigation should be extended to assess the effectiveness of omega-3 and zinc versus vitamin C, omega-3 and vitamin C versus zinc, and finally omega-3 alone versus zinc and vitamin C on peri-implant bone density in the same age and sex-matching currently included population
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Oral-Radiology
Issued also as CD
Keywords: Effectiveness; Histopathological; Mechanism